Peran Wakaf Produktif Dalam Pemberdayaan Kemandirian Ekonomi Pondok Pesantren (Studi kasus Pesantren Tebuireng Yayasan Hasyim Asyari Jombang) - Muhammad Widyarta Wijaya; Raditya Sukmana (Universitas Airlangga, 2019)
This study aims to describe the role of productive endowments in economic empowerment of Islamic boarding schools. This study used qualitative research methods. The analysis technique used is descriptive with a case study method in which this research is conducted by conducting interviews, documentation and direct observation. The results of the study show that the Nazi Hasyim Asyari Foundation has managed 7 productive waqf units which focus on the local unit of teaching and learning very well as seen from the average monthly profit of around 2.2 billion Rupiah. The profit is allocated 80% for the development of Islamic boarding schools and 20% for scholarships amounting to 80% of elementary school students, 75% of santri Mualimin and 100% for students. Scholarships are only given to classical education units on ideological grounds. All funding for all activities at the Tebuireng Islamic Boarding School comes from the income of productive waqf units which are supervised and developed by the Hasyim Asyari FoundationKeywords: waqf, productive waqf, productive waqf units, productive waqf roles, nazhir Hasyim Asyari FoundationREFFERENCESDepartemen Agama. 2003. Fiqh Waqf. Jakarta: Direktorat Pemberdayaan Wakaf Direktorat Jendral Bimbingan Masyarakat Islam Departemen Agama RI.Emzir. 2012. Metodologi Penelitian Kualitatif: Analisis Data. Jakarta: PT. Raja Grafindo Persada.Farhana, Mohamad. Suhaimi, Asmak. Rahman, Ab. Sabitha, Marican , (2014),